An absorbing short-wave blue light and heat-proof film, a preparation method thereof and application as a lens
Patent Information
- Application Number
- CN202611021727.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]首先,现有防蓝光反射膜未能解决背面蓝光反射入眼问题:反射膜能有效将前方入射的蓝光反射回去,但从背面、侧后方入射的蓝光则反射进入眼睛
本发明提供的防蓝光膜具有多级蓝光吸收机制,通过调控碳点表面官能团实现:1)400-440nm短波蓝光吸收率>98%(量子产率0.92);2)440-480nm长波蓝光透过率≥90%。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of optical materials technology, specifically to an absorptive anti-shortwave blue light and anti-heat film, its preparation method, and its application as a lens. Background Technology
[0002] As is well known, the visible light emitted by various computer and television screens, energy-saving lamps, and other new artificial light sources contains a large amount of short-wavelength blue light with irregular frequencies. Long-term exposure to blue light can penetrate the lens and reach the retina, causing photochemical damage and thus affecting vision. High-energy short-wavelength blue light is one of the factors that cause eye fatigue.
[0003] Specifically, short-wavelength blue light (400-440 nm) transmitted through eyeglass lenses, with photon energies as high as 2.82-3.10 eV, can penetrate the lens and trigger photo-oxidation reactions in the retina. In children under 10 years old, the lens transmission window can extend to 320 nm (UV-B band), and exposure to a wider spectrum in adolescents can lead to dual damage to the retina from both UV-B and short-wavelength blue light. Clinical trials have confirmed (Narimatsu et al., Clin Exp Ophthalmol 2014) that continuous exposure to this type of radiation can increase the apoptosis rate of retinal pigment epithelial cells, constituting a major contributing factor to macular degeneration.
[0004] Modern lens coating technology mostly uses multi-layer film technology to achieve blue light reflection and largely prevents blue light from directly entering the eye. However, there is still room for improvement in the precise control of wavelength.
[0005] First, existing blue light reflective films fail to address the issue of blue light reflecting into the eyes from the back: while the reflective film effectively reflects blue light incident from the front, it reflects blue light incident from the back or rear side into the eyes. Therefore, a more ideal protection technology would be short-wavelength blue light absorption.
[0006] Secondly, existing blue light filtering films fail to resolve the spectral selection dilemma: while short-wavelength blue light (400-440 nm) has a significant impact on the lens, long-wavelength blue light (446-477 nm) is essential for inducing melatonin secretion, which is related to circadian rhythms. Therefore, ideal protection requires both high absorption of short-wavelength blue light and high transmittance of long-wavelength blue light.
[0007] Finally, common blue light absorbing materials fail to solve the heat generation problem: lenses generate heat after absorbing blue light with high photon energy. Prolonged heat generation not only affects the lens's refractive index but also significantly reduces the lifespan of the lens and its thin film. Therefore, an ideal blue light absorbing material needs to emit energy promptly while absorbing it, thus avoiding heat generation. Summary of the Invention
[0008] The technical problem to be solved by this invention is how to improve the blue light blocking performance of lenses.
[0009] The present invention solves the above-mentioned technical problems through the following technical means: An absorptive anti-shortwave blue light and anti-heat film comprises nanoporous glass and fluorescent carbon dots uniformly embedded in the pores of the nanoporous glass; the pore size of the nanoporous glass is 2-50 nm; the particle size of the fluorescent carbon dots is 5-8 nm, and the fluorescence peak emission value is 520 nm when excited by a laser with a wavelength of 405 nm.
[0010] Preferably, the nanoporous glass comprises a glass substrate and a nanoporous layer located on the glass substrate; the porosity of the nanoporous layer is ≥80%.
[0011] Preferably, the pore size of the nanoporous layer is 30-50 nm.
[0012] Preferably, the thickness of the nanoporous layer is 20±2μm.
[0013] Preferably, the glass substrate is one or a composite of two of the following: inorganic glass substrate and organic glass substrate.
[0014] Preferably, the inorganic glass substrate is one or both of the following: SiO2-TiO2-ZrO2 ternary system glass and Bi2O3-B2O3 system glass.
[0015] Preferably, the plexiglass substrate is an plexiglass substrate prepared by coupling mercaptosilane and in-situ polymerization of epoxy resin.
[0016] Preferably, the nanoporous glass is prepared using a dual-template pore-forming method; specifically, it includes the following steps: S1. PMMA microspheres were ultrasonically dispersed in an ethanol solution and mixed with Pluronic F127 aqueous solution to obtain a PMMA / F127 dual template suspension; tetraethyl orthosilicate, aluminum isopropoxide and zinc acetate were mixed and hydrolyzed under acidic catalytic conditions to form a SiO2-Al2O3-ZnO ternary sol. S2. The SiO2-Al2O3-ZnO ternary sol and PMMA / F127 dual template suspension are mixed evenly and then deposited onto the surface of the activated glass substrate by spin coating; the activated glass substrate is obtained by treating the glass substrate with O2 plasma. S3. The product from S2 is placed in a constant temperature and humidity environment to form a three-dimensional inorganic gel network, then exposed to ether vapor, and then subjected to heat treatment, acid etching, cleaning, and drying to obtain the nanoporous glass.
[0017] Preferably, in S1, the PMMA microspheres have a diameter of 15±3 nm; the PMMA microspheres are ultrasonically dispersed in an ethanol solution at a concentration of 25 mg / mL; the ethanol solution is a 50% (v / v) aqueous ethanol solution; the ultrasonic dispersion power is 120 watts and the time is 30 minutes.
[0018] Preferably, in S1, the concentration of the Pluronic F127 aqueous solution is 25 mg / mL; and the mixing temperature is 35°C.
[0019] Preferably, in S1, the mass ratio of PMMA microspheres to Pluronic F127 is 0.8-1.5:1; more preferably 1:1.
[0020] Preferably, in S1, the molar ratio of tetraethyl orthosilicate, aluminum isopropoxide, and zinc acetate is 75:15:10; the stirring hydrolysis temperature is 45°C, and the time is 4 hours.
[0021] Preferably, in S2, the O2 plasma treatment power is 300 watts and the time is 10 minutes.
[0022] Preferably, in S2, the volume ratio of SiO2-Al2O3-ZnO ternary sol to PMMA / F127 dual template suspension is between 1:1 and 1:1.5.
[0023] Preferably, the concentration of PMMA microspheres in the PMMA / F127 dual-template suspension is 10-30 mg / mL; more preferably 10-15 mg / mL; and more preferably 12.5 mg / mL.
[0024] Preferably, in S2, the rotation speed is 2500 rpm during the spin coating process.
[0025] Preferably, in S3, a three-dimensional inorganic gel network is formed by maintaining the environment at a constant temperature and humidity of 45°C and 75% RH for 8 hours.
[0026] Preferably, in S3, the exposure time to ether vapor is 1 minute.
[0027] Preferably, in S3, the heat treatment includes holding at 280°C in an air atmosphere for 60 minutes, then holding at 450°C in a nitrogen protective atmosphere for 90 minutes, and then sintering in a vacuum environment at 580°C for 120 minutes.
[0028] Preferably, in S3, the acid etching includes etching for 45 minutes using a mixed acid solution of hydrochloric acid and hydrofluoric acid.
[0029] Preferably, the method for preparing the fluorescent carbon dots includes the following steps: S1. Dissolve zinc nitrate and 2-methylimidazole in methanol and stir at room temperature to obtain ZIF-8 precursor powder; S2. The ZIF-8 precursor powder was pyrolyzed under an inert atmosphere. After cooling to room temperature, the product was immersed in HCl solution and stirred. After washing and drying, nitrogen-doped carbon dot powder was obtained. S3. The nitrogen-doped carbon dot powder is subjected to plasma treatment under a mixed gas of argon and ammonia to obtain the fluorescent carbon dots.
[0030] Preferably, in the preparation of fluorescent carbon dots, in S1, the molar ratio of zinc nitrate to 2-methylimidazole is 1:1; the stirring time is 6 hours; in S2, the heating pyrolysis includes heating to 400-450°C at a rate of 2-5°C / min and holding at this temperature for 1-2 hours; continuing to heat to 800-900°C and holding at this temperature for 1 hour; the stirring temperature is 80°C and the time is 12-24 hours; in S3, the volume ratio of argon to ammonia (Ar:NH3) is between 4:1 and 1:1; radio frequency or microwave plasma is used for treatment, with a power of 50-150 watts, a temperature of room temperature to 80°C, and a vacuum maintained at a low pressure of 10-100 Pa for 5-30 minutes.
[0031] Preferably, the absorbent anti-shortwave blue light and anti-heat film has the following optical performance: absorption rate > 98% in the 400-440nm band and transmittance ≥ 90% in the 440-480nm band.
[0032] The present invention also proposes a method for preparing the aforementioned absorption-type anti-shortwave blue light and anti-heat film, comprising the following steps: immersing nanoporous glass in a fluorescent carbon dot ethanol solution, permeating under vacuum pressure, centrifuging, and then curing under ultraviolet light to form a cross-linked film layer to obtain the aforementioned absorption-type anti-shortwave blue light and anti-heat film.
[0033] Preferably, the nanoporous glass is nanoporous glass that has been plasma cleaned.
[0034] Preferably, the nanoporous glass is vertically immersed in a fluorescent carbon dot ethanol solution, followed by ultrasonic permeation under vacuum pressure.
[0035] Preferably, after centrifugation, a silane coupling agent containing double bonds is added as a crosslinking aid before UV curing.
[0036] Preferably, after centrifugation, the mixture is further flash-evaporated at 50°C for 30 seconds.
[0037] Preferably, the concentration of fluorescent carbon dots in the fluorescent carbon dot ethanol solution is 15 mg / mL; the vacuum pressure osmosis pressure is 0.1 MPa and the temperature is 60°C; the UV curing conditions include 365 nm and 10 nm. Irradiate for 3 minutes under the condition of / cm².
[0038] The present invention also proposes the application of the aforementioned absorption-type anti-shortwave blue light and anti-heat film in lenses.
[0039] The present invention also proposes an absorptive anti-shortwave blue light and anti-heat lens, including the aforementioned absorptive anti-shortwave blue light and anti-heat film.
[0040] Preferably, the absorbent anti-shortwave blue light and anti-heat lens has a photothermal conversion efficiency of ≤3%, a temperature rise of <0.5℃, a haze value of ≤0.4%, and a 400-440nm blue light global absorption rate of >98% when the incident light viewing angle is ≥160°.
[0041] The advantages of this invention are: The blue light blocking film provided by this invention has a multi-level blue light absorption mechanism, which is achieved by regulating the functional groups on the surface of carbon dots: 1) absorption rate of short-wavelength blue light in the 400-440nm range > 98% (quantum yield 0.92); 2) transmittance of long-wavelength blue light in the 440-480nm range ≥ 90%.
[0042] The lens provided by this invention has a heat dissipation structure, and the excited state electrons of carbon dots release energy through non-radiative transitions (fluorescence peak 520nm), achieving a photothermal conversion efficiency of ≤3% and a lens temperature rise of <0.5℃ (ISO 18526 standard test).
[0043] The lens provided by this invention has an all-directional protection enhancement effect: unlike the one-way protection defect of reflective films, this structure achieves full-range absorption of blue light incident from the front, back and sides (viewing angle ≥160°).
[0044] Furthermore, this invention also provides the application of the aforementioned absorptive blue light blocking lenses in eyeglasses and other virtual imaging devices. It solves three major shortcomings of traditional technologies: 1) eliminating the risk of blue light transmission from the back; 2) accurately separating the biorhythm wavelength band from the damage wavelength band; and 3) overcoming the bottleneck of thermal accumulation in absorptive materials. Attached Figure Description
[0045] Figure 1 This is a schematic diagram illustrating the optical properties of the lens of the present invention. Figure 2 This is a schematic diagram of the structure of the absorption-type anti-shortwave blue light and anti-heat-reducing lens based on uniform nano carbon dots of the present invention; wherein, 1 is the substrate, 2 is a porous glass layer with uniformly dispersed carbon dots, 3 is a nanoporous glass layer, and 4 is uniformly distributed nano carbon dots. Figure 3 The emission spectrum of carbon dots under 405nm laser excitation in Example 1 of this invention; Figure 4 This is a schematic diagram illustrating the wavelength-dependent function of the absorption-type anti-shortwave blue light and anti-heat lens of the present invention. Detailed Implementation
[0046] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0047] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available.
[0048] Unless otherwise specified in the embodiments, the techniques or conditions described in the literature in this field or in accordance with the product manual may be followed.
[0049] Example 1: Preparation of an absorption-type anti-shortwave blue light and anti-heat film, the structural schematic diagram of which is shown below. Figure 2 As shown; The glass substrate materials suitable for this invention can be inorganic glass substrates represented by the SiO2-TiO2-ZrO2 ternary system and the Bi2O3-B2O3 high refractive index system; it is also suitable for organic glass substrates represented by mercaptosilane coupling and epoxy resin in-situ polymerization; in this embodiment, the SiO2-TiO2-ZrO2 ternary system is selected. (1) Preparation process of fluorescent carbon dots (N-CDs) The fluorescent carbon dots (N-CDs) in this embodiment were prepared according to the following process: 1) High specific surface area nitrogen-doped carbon dots (N-CDs) were prepared using zinc zeolite imidazole ester framework (ZIF-8) as a precursor. Precursor synthesis and optimization: Zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 2-methylimidazole (2-Melm) were dissolved in methanol, with a molar ratio of zinc nitrate hexahydrate to 2-methylimidazole of 1:1 and a molar ratio of zinc nitrate hexahydrate to methanol of 1 g: 68 ml. The mixture was rapidly mixed and stirred continuously at room temperature for a certain period of time (6 hours) to obtain a ZIF-8 nanocrystal suspension.
[0050] Washing and drying: The white precipitate was collected by centrifugation, washed repeatedly with methanol to remove unreacted substances, and then dried overnight in a vacuum drying oven at 60°C to obtain ZIF-8 precursor powder.
[0051] Controlled pyrolysis and carbonization: Under an inert atmosphere (high-purity nitrogen or argon; nitrogen is used in this embodiment), a programmed temperature-increasing pyrolysis is performed. First, the temperature is increased to 400-450°C at a rate of 2-5°C / min and held at this temperature for 1-2 hours (in this embodiment, the temperature is increased to 400°C at a rate of 2°C / min and held at this temperature for 1 hour). This step is the crucial carbonization stage, where the ZIF-8 framework collapses and transforms into nitrogen-doped carbon, while zinc species are reduced and partially evaporated, acting as a "self-template" for pore formation. The temperature is then increased further to 800-900°C (optional, for further graphitization and conductivity adjustment) and held for 1 hour (in this embodiment, the temperature is further increased to 800°C and held for 1 hour).
[0052] Acid washing and purification: After the reactor cools to room temperature, remove the black product. Immerse it in 1M HCl solution and stir at 80°C for 12-24 hours (12 hours at 80°C in this example) to completely dissolve the residual zinc or zinc oxide nanoparticles.
[0053] Post-treatment: Wash with deionized water until neutral, then vacuum dry at 80°C to obtain the final nitrogen-doped carbon dots (N-CDs) powder.
[0054] 2) Biological templates (such as silk fibroin) can also be used to prepare fluorescent carbon dots (N-CDs) through reaction heating. First, a silk fibroin precursor solution needs to be prepared. Silkworm cocoons are typically used as raw material. The cocoons are boiled in a sodium carbonate solution to degummify them, completely removing the outer layer of sericin and leaving pure silk fibers. These fibers are then dissolved in a lithium bromide solution and dialyzed to remove salts, ultimately yielding an aqueous silk fibroin solution.
[0055] Hydrothermal reaction: The pH of the silk fibroin aqueous solution is adjusted to alkaline (e.g., 9.0). Then, the solution is placed in an oven at 180 degrees Celsius for 12 hours. Under these conditions, the silk fibroin undergoes hydrolysis, deamidation, and carbonization, forming carbon dots.
[0056] After the reaction is complete, the product needs to be purified through multiple steps of filtration, chromatography and dialysis to remove byproducts and enrich the target carbon dots. Fluorescent carbon dot solid powder can be obtained by freeze drying.
[0057] 3) Fluorescent carbon dots (N-CDs) can also be prepared using a chlorophyll-Mg template and a biomimetic synthesis method. First, chlorophyll was extracted from fresh green leaf material using acetone solution in the dark. To enhance the metal centers, magnesium chloride was added to the extract to promote the formation of a stable chlorophyll-magnesium complex, which was then purified by chromatography to provide a homogeneous precursor for subsequent reactions.
[0058] Microwave synthesis: The purified chlorophyll-Mg complex was dissolved in ethanol and placed in a microwave reactor. Irradiation at a high power of 900 watts for 3 minutes caused a rapid increase in solution temperature, resulting in a violent and rapid breakage and recombination of the chlorophyll macromolecule structure. This rapid pyrolysis process immobilizes magnesium atoms in situ within the structure of newly formed carbon points, effectively altering its electronic band structure and ultimately achieving a significant redshift of approximately 32 nanometers in the absorption spectrum.
[0059] The reaction was immediately cooled, and the carbon dots were separated and purified by centrifugation, filtration and column chromatography to remove unreacted chlorophyll and byproducts, thus obtaining fluorescent carbon dots.
[0060] 4) Fluorescent carbon dots (N-CDs) can also be prepared based on the continuous flow production of citric acid pyrolysis. Precursor solution preparation and pretreatment: High-purity (≥99.0%) citric acid (CA) was selected as the main carbon source, and L-cysteine (L-Cys) was used as a synergistic carbon, nitrogen, and sulfur source. Ultrapure water (resistivity ≥18.2 MΩ·cm) was used as the solvent to minimize the interference of impurities such as metal ions on fluorescence performance. Under nitrogen protection or continuous stirring, the calculated masses of citric acid and L-cysteine were sequentially dissolved in ultrapure water. A homogeneous and clear solution with a final concentration of 0.8 M citric acid and 0.3 M L-cysteine was prepared. This molar ratio (CA : L-Cys ≈ 2.7:1) aims to ensure sufficient carbon framework formation while providing adequate N and S doping atoms. The prepared precursor solution is filtered through a 0.22 μm polyethersulfone (PES) membrane to remove any particulate matter or microorganisms, and then transferred to a feed tank where an inert gas (such as nitrogen or argon) is introduced to remove dissolved oxygen. This anaerobic environment helps prevent unnecessary oxidation side reactions of the precursor during the preheating stage.
[0061] Continuous pyrolysis reaction process: A continuous flow tubular reactor or microchannel reactor is used. The system mainly consists of a high-pressure feed pump, a preheating section, a reaction tube section (placed in a precision temperature-controlled furnace), a back pressure regulating valve, a cooler, and a product collection tank. A high-precision, high-pressure plunger pump is used to pump the precursor solution into the system at a constant flow rate (0.1-50 ml / min). The solution first flows through the preheating section and is rapidly heated to near the reaction temperature (e.g., 180-200℃), ensuring it is close to pyrolysis before entering the main reaction zone. The preheated mixture enters the isothermal reaction tube section, where the reaction temperature is 220℃, the system pressure is 4.0 MPa, and the reaction time is 120 seconds. The effluent from the reaction is immediately quenched instantly through a high-efficiency heat exchanger (cooler) (dropping to below 50℃ within seconds) to terminate the reaction, prevent further growth or aggregation of carbon points, and thus lock their size and surface state.
[0062] Product Collection and Purification: The quenched crude product solution first flows through a pre-filter (e.g., 5 μm) to remove possible trace solid impurities, and then enters a tangential flow filtration system. The filtration system uses an ultrafiltration membrane with a molecular weight cutoff of 100 kDa to remove unreacted small molecule precursors, salt byproducts, and oligomers that are too small, while simultaneously concentrating the product. The purified and concentrated carbon dot dispersion is then removed and rapidly deep-frozen at -80°C or in liquid nitrogen, and then placed in a freeze dryer for sublimation under low temperature (<-50°C) and high vacuum conditions to remove moisture, finally yielding a fluffy solid nitrogen / sulfur co-doped carbon dot powder.
[0063] (2) Surface amination treatment of fluorescent carbon dots (N-CDs) Argon / ammonia mixed plasma surface amination treatment was performed to introduce high-density amino groups (-NH2) on the surface of N-CDs without severely damaging their carbon skeleton structure. The target surface amino density was 8.7 mmol / g.
[0064] Sample pretreatment: The N-CDs powder obtained in step 1) using zinc zeolite imidazole ester framework (ZIF-8) as a precursor was uniformly spread on the sample stage of the plasma reactor. The reaction chamber was evacuated and argon gas was introduced for several "gas washing" cycles to eliminate interference from air (especially oxygen and water vapor).
[0065] Plasma activation: Under mixed gas conditions of argon (Ar) and ammonia (NH3) (typical volume ratios can be optimized between Ar:NH3 = 4:1 and 1:1. Argon primarily generates high-energy particles that bombard the surface to create active sites, while ammonia provides the nitrogen source), radio frequency (RF) or microwave ( Plasma, power 50-150 watts, temperature room temperature or slightly higher (<80℃), vacuum maintained at a low pressure of 10-100 Pa for 5-30 minutes. Specifically, in this embodiment, under mixed gas conditions of argon (Ar) and ammonia (NH3) (volume ratio Ar:NH3=4:1), microwave treatment is employed. Plasma, power 50 watts, temperature room temperature, vacuum maintained at a low pressure of 10-100 Pa, for 30 minutes; Post-processing and preservation: After plasma activation treatment, the sample was cooled under continuous purging of inert argon gas to obtain fluorescent carbon dots.
[0066] The luminescence spectrum of carbon dots under 405nm laser excitation is as follows Figure 3 As shown.
[0067] (3) Preparation of nanoporous glass layers using a dual-template pore-forming method ① Construction of dual templates and preparation of mixed sol: Construct a template system for multi-scale synergistic pore formation and prepare an inorganic precursor solution.
[0068] Hard template construction: Monodisperse PMMA microspheres (15±3 nm in diameter) were ultrasonically dispersed in a 50% (v / v) ethanol solution at a concentration of 25 mg / mL (120 W, 30 min) to form a stable and homogeneous suspension. These microspheres will serve as macroscopic site-filling agents for macropores (>50 nm) in subsequent processes.
[0069] Soft template introduction: Simultaneously, the amphiphilic block copolymer Pluronic F127 was prepared into an aqueous solution (concentration 25 mg / mL). F127 molecules self-assemble in solution to form micelles. The hydrophobic core (PPO segments) has a certain affinity for the PMMA microsphere surface, while the hydrophilic shell (PEO segments) tends to extend into the aqueous phase. The two templates are mixed under specific conditions (35°C) (hard template to soft template volume ratio: 0.8-1.5:1, preferably 1:1 in this embodiment). The F127 micelles can adsorb or surround the PMMA microsphere surface, forming a "microsphere-micelle" composite template to obtain a PMMA / F127 dual-template suspension.
[0070] Preparation of inorganic network precursor: Tetraethyl orthosilicate (TEOS), aluminum isopropoxide, and zinc acetate were mixed in a precise molar ratio (75:15:10) and hydrolyzed under acidic catalytic conditions (0.01M HNO3, pH≈3.0) at 45°C with stirring for 4 hours to form a clear and stable SiO2-Al2O3-ZnO ternary sol. This sol serves as the source of the inorganic framework.
[0071] ② Substrate pretreatment and composite template spin coating: Ensure that the sol is evenly spread on the substrate and assembled with the template.
[0072] Substrate activation: The glass substrate is treated with O2 plasma (300 watts, 10 minutes) to make its surface hydrophilic and rich in hydroxyl groups, which significantly improves the wettability and adhesion of the sol.
[0073] Composite Coating: The prepared ternary sol and the prepared PMMA / F127 dual-template suspension were mixed uniformly at a volume ratio between 1:1 and 1:1.5; in this embodiment, 1:1 was selected. The mixture was then immediately deposited onto the activated glass substrate surface via spin coating. Under the combined effect of centrifugal force generated by high-speed rotation (2500 rpm) and rapid solvent evaporation, the inorganic precursors in the sol and the dual-template underwent synergistic self-assembly on the substrate: PMMA microspheres tended to be densely packed, while F127 micelles filled the gaps between the microspheres or adsorbed onto their surface, forming a highly ordered temporary composite structure.
[0074] ③ Gelification and phase separation solidification of the inorganic framework: solidify the inorganic network and lock the template structure.
[0075] Controlled gelation: The spin-coated wet film was placed in a constant temperature and humidity environment (45℃, RH 75%) for 8 hours. Under these conditions, the silicon, aluminum, and zinc species in the sol further hydrolyzed and condensed, gradually forming a three-dimensional inorganic gel network. This network encapsulated and fixed the arrangement of PMMA microspheres and F127 micelles.
[0076] Phase separation triggering: Short-term exposure to ether vapor (1 minute) acts as a trigger to accelerate microphase separation in the system, making the interface between the inorganic phase and the organic template phase clearer, thus laying the foundation for the subsequent formation of clear pore walls.
[0077] ④ Stepped heat treatment to remove template and densify skeleton: Remove organic template and strengthen inorganic skeleton.
[0078] Low-temperature degreasing: The process involves holding the product at 280℃ in air for 60 minutes. This stage primarily decomposes and removes the F127 soft template and some organic residues, forming a mesoporous (2-50nm) structure surrounded by an inorganic framework.
[0079] Medium-temperature pre-firing: The substrate is heated to 450℃ in a nitrogen protective atmosphere for 90 minutes. This stage primarily decomposes and removes the PMMA hard template microspheres, leaving behind large pores (approximately 45nm) formed by their placement. The nitrogen atmosphere prevents the framework from being oxidized at high temperatures.
[0080] High-temperature sintering: in a vacuum environment at 580℃ (10 - Sintering at 3Pa for 120 minutes. This stage further densifies and crystallizes the inorganic framework (SiO2-Al2O3-ZnO), enhancing its mechanical strength and chemical stability, ultimately forming a stable dual-scale (macropore + mesopore) composite porous structure.
[0081] ⑤ Selective acid etching to optimize pore connectivity and structure characterization: Optimizing pore connectivity and purity Acid etching: Etching was performed for 45 minutes using a mixture of HF (47% by mass) and HCl (37% by mass) (volume ratio 4:1) to selectively remove some amorphous silicon phase or residual impurities, further opening and unblocking pores, and improving pore connectivity and specific surface area.
[0082] Cleaning and drying: After acid etching, ultrasonically clean with deionized water (40kHz, 20 minutes) to thoroughly remove etching products and residual reagents, and then dry.
[0083] In (3), the preparation method of the glass layer nanoporous structure can also employ electrochemical deposition technology, including the following steps: Using the aforementioned glass substrate, a pretreatment was first performed using O2 plasma etching (100 watts, 5 min) to improve surface properties.
[0084] Electrochemical pore etching is then performed in two steps. First, the prepared ternary sol is mixed uniformly with the prepared PMMA / F127 dual-template suspension at a volume ratio of 1:1. This mixture is held at a constant potential of -1.2V (vs Ag / AgCl) for 30 seconds. This negative potential drives the preferential reduction and deposition of zinc ions in the solution on the electrode surface, forming a uniform and dense zinc silicate seed layer. This seed layer serves not only as the nucleation site for subsequent three-dimensional growth but also defines the initial pore distribution. Subsequently, periodic pulse voltages of +0.8V / -1.5V are applied for 1000 cycles. The +0.8V positive pulse causes controlled anodic dissolution of the silicon / zinc species, creating pores around the F127 micelle template; the subsequent -1.5V negative pulse drives the rapid deposition and growth of zinc silicate on the surface of the previously formed pore framework. Through this repeated cycle of "dissolution-deposition," a stable framework with three-dimensional interconnected channels and a multi-level structure is finally formed on the glass substrate.
[0085] (4) Composite process of carbon dots and nanoporous glass The process consists of the following four steps: 1) Substrate Pretreatment and Solution Immersion: The obtained porous glass substrate was subjected to plasma cleaning to activate the surface hydroxyl groups and enhance its hydrophilicity. A carbon dot ethanol dispersion with a concentration of 15 mg / ml was prepared. The pretreated substrate was vertically immersed in the prepared carbon dot solution and treated with ultrasound for 5 minutes to initially remove air bubbles in the pores, promote solution wetting, and initiate capillary penetration into the nanopores.
[0086] 2) Vacuum Hot-Pressure Permeation Enhanced Filling: The impregnated sample is transferred to a vacuum chamber. A vacuum is first drawn to below 10 Pa at 60°C and maintained for 10 minutes to completely remove residual gas from the pores. Then, dry nitrogen gas is slowly introduced into the chamber to 0.1 MPa (gauge pressure), and the chamber is held at this pressure for 30 minutes. This process utilizes the pressure difference to drive the carbon dot solution to fill deep nanopores. Increasing the temperature reduces the solution viscosity, improves permeation efficiency, and ensures a more uniform distribution of carbon dots within the pores.
[0087] 3) Centrifugation Cleaning and Preliminary Curing: After infiltration, the sample is centrifuged at 3000 rpm for 5 minutes to remove excess physically adsorbed carbon dots from the surface and large pores, preventing the formation of an excessively thick, uneven layer. Immediately after centrifugation, the sample is placed on a 50°C hot plate for flash evaporation for 30 seconds to quickly remove residual ethanol from the surface, allowing carbon dots to initially accumulate in the pore area. This step lays the foundation for subsequent photocuring to form a regular interface layer.
[0088] 4) UV crosslinking and curing film formation: The sample is placed under 365nm UV light at a light intensity of 10m. Irradiate for 3 minutes at a temperature of / cm². Before irradiation, a small amount of silane coupling agent (MAPTMS) containing double bonds can be dropped onto the sample surface as a crosslinking aid. UV light excites the carbon dots to generate active free radicals, initiating covalent crosslinking between the functional groups on the carbon dot surface and the coupling agent and silanol groups on the pore walls, forming a stable three-dimensional network structure at the pore inlet and inside. After curing, the sample is purged with nitrogen gas to finally obtain structurally stable carbon dots. The optical principle diagram of the glass composite functional layer, namely the absorption-type anti-shortwave blue light and anti-heat lens, is shown in the figure below. Figure 1 As shown; Wavelength-dependent functional diagram as shown Figure 4 As shown.
[0089] (5) Lens performance test 1) Accelerated aging test (equivalent to 3 years of use): Blue light shielding stability: After the lens was exposed to 85℃ / 85RH for 1000 hours, the absorption rate in the 400-440nm band decreased by <0.3%; Thermal deformation control: The lens is placed under laser irradiation (150m). After 1 hour (at 405nm), the lens deformation was <0.05%; Mechanical strength: The coating adhesion of the lens reaches grade 5B (ASTM D3359), and the abrasion resistance is ≥8H (ISO 12137).
[0090] 2) Biological validation (in accordance with ISO 12312-3:2022): Retinal protection: Under simulated screen lighting, the apoptosis rate of human retinal pigment epithelial cells (ARPE-19) decreased from 21.3% to 4.7%.
[0091] Circadian rhythm maintenance: When the transmittance of light in the 440-480nm band is 91.5%, the melatonin secretion rhythm deviation is <5% (vs natural light).
[0092] This invention provides an absorptive anti-shortwave blue light and anti-heat coating structure and lens; the coating structure consists of a nanoporous glass layer (porosity ≥80%) and uniformly embedded fluorescent carbon dots (particle size 5-8nm), and has the following characteristics: 1) The spectral selective absorption mechanism achieves an absorption rate of >98% for short-wavelength blue light in the 400-440nm range and a transmittance of ≥90% for long-wavelength blue light in the 440-480nm range, simultaneously blocking retinal damage and maintaining biological rhythms. 2) The heat dissipation-fluorescence conversion system releases energy through non-radiative transitions of carbon dots (fluorescence peak 520nm), with a lens photothermal conversion efficiency ≤3% and a temperature rise <0.5℃; 3) The omnidirectional protection architecture achieves full-range absorption of blue light incident from the front, back, and sides (viewing angle ≥160°). After accelerated aging testing, the absorption rate attenuation in the 400-440nm band is <0.3%, and the film adhesion is rated 5B. It is suitable for glasses and virtual imaging devices, breaking through the three major technical bottlenecks of traditional reflective films: unidirectional protection limitations, spectral modulation imbalance, and heat deformation.
[0093] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An absorptive anti-shortwave blue light and anti-heat film, characterized in that: It comprises nanoporous glass and fluorescent carbon dots uniformly embedded in the pores of the nanoporous glass; the pore size of the nanoporous glass is 2-50 nm; the particle size of the fluorescent carbon dots is 5-8 nm, and the emission fluorescence peak is 520 nm when excited by a laser with a wavelength of 405 nm.
2. The absorption-type anti-shortwave blue light and anti-heat film according to claim 1, characterized in that: The nanoporous glass comprises a glass substrate and a nanoporous layer located on the glass substrate; the porosity of the nanoporous layer is ≥80%.
3. The absorption-type anti-shortwave blue light and anti-heat film according to claim 1, characterized in that: The nanoporous glass is prepared using a dual-template pore-forming method; specifically, it includes the following steps: S1. PMMA microspheres were ultrasonically dispersed in an ethanol solution and mixed with Pluronic F127 aqueous solution to obtain a PMMA / F127 dual template suspension; tetraethyl orthosilicate, aluminum isopropoxide and zinc acetate were mixed and hydrolyzed under acidic catalytic conditions to form a SiO2-Al2O3-ZnO ternary sol. S2. The SiO2-Al2O3-ZnO ternary sol and PMMA / F127 dual template suspension are mixed evenly and then deposited onto the surface of the activated glass substrate by spin coating; the activated glass substrate is obtained by treating the glass substrate with O2 plasma. S3. The product from S2 is placed in a constant temperature and humidity environment to form a three-dimensional inorganic gel network, then exposed to ether vapor, and then subjected to heat treatment, acid etching, cleaning, and drying to obtain the nanoporous glass.
4. The absorption-type anti-shortwave blue light and anti-heat film according to claim 1, characterized in that: The method for preparing the fluorescent carbon dots includes the following steps: S1. Dissolve zinc nitrate and 2-methylimidazole in methanol and stir at room temperature to obtain ZIF-8 precursor powder; S2. The ZIF-8 precursor powder was pyrolyzed under an inert atmosphere. After cooling to room temperature, the product was immersed in HCl solution and stirred. After washing and drying, nitrogen-doped carbon dot powder was obtained. S3. The nitrogen-doped carbon dot powder is subjected to plasma treatment under a mixed gas condition of argon and ammonia to obtain the fluorescent carbon dots.
5. A method for preparing an absorptive anti-shortwave blue light and anti-heat film as described in any one of claims 1-4, characterized in that: Includes the following steps: The nanoporous glass was immersed in a fluorescent carbon dot ethanol solution, and then permeated under vacuum pressure. After centrifugation, it was cured under ultraviolet light to form a cross-linked film layer, thus obtaining the absorption-type anti-shortwave blue light and anti-heat film.
6. The method for preparing the absorption-type anti-shortwave blue light and anti-heat film according to claim 5, characterized in that: After centrifugation, a silane coupling agent containing double bonds is added as a crosslinking aid before UV curing.
7. The method for preparing the absorption-type anti-shortwave blue light and anti-heat film according to claim 5 or 6, characterized in that: The concentration of fluorescent carbon dots in the ethanol solution was 15 mg / mL; the vacuum pressure osmosis pressure was 0.1 MPa and the temperature was 60 °C; the UV curing conditions included 365 nm and 10 nm. Irradiate for 3 minutes under the condition of / cm².
8. The application of an absorptive anti-shortwave blue light and anti-heat film as described in any one of claims 1-4 in a lens.
9. An absorptive type anti-shortwave blue light and anti-heat lens, characterized in that: Including the absorption-type anti-shortwave blue light and anti-heat film as described in any one of claims 1-4.
10. The absorption-type anti-shortwave blue light and anti-heat-reducing lens according to claim 9, characterized in that: Its photothermal conversion efficiency is ≤3%, temperature rise is <0.5℃, haze value is ≤0.4%, and when the incident light viewing angle is ≥160°, the global absorption rate of blue light in the 400-440nm range is >98%.